Assessment of past and future potential of ocean wave power in the Gulf of Guinea - Dahunsi, A.M.; Foli, B.A.K. (INTERNATIONAL JOURNAL OF SUSTAINABLE ENGINEERING, 2023)
the aim of identifying high-density wave energy locations for potential exploitation. To estimate wave power density (WPD) for three time periods (past: 1979–2005, mid-century: 2026–2050, and end-century: 2081–2100), we utilized significant wave height and mean wave period obtained from eight General Circulation Models. Using an ensemble of these WAVEWATCH III simulated datasets, we calculated WPD and assessed overall and seasonal trends, projecting changes under Representative Concentration Pathway (RCP) 4.5 and 8.5 scenarios. Results revealed higher potential WPD in the western GoG, particularly near the coast, with increased values offshore. Spatially, WPD change rates varied widely (−0.021 to 0.039 kW/m per year), suggesting both positive and negative trends, though generally low. Projections indicated a potential increase from 0.5 to 1.0 kW/m by the end of the century. The estimated potential power for harvesting exceeded 14,000 MW, with offshore regions showing better wave con verter performance. This study concludes that GoG's wave energy is a promising renewable resource, offering a potential solution to future power needs and contributing to regional greenhouse gas emission mitigation.
Research Article
Keywords: Gulf of Guinea; wave power; Renewable energy; climate change; RCP scenarios